Effects of COVID-19 vaccines on patient-reported outcomes in patients with inflammatory bowel disease: a multicenter survey study in Korea - Ji, Jung Hyun; Shin, Seung Hwan; Park, Yong Eun; Park, Jihye; Park, Jae Jun; Cheon, Jae Hee; Kim, Tae Il; Kang, Sang-Bum; Park, Sang Hyoung; Park, Soo Jung (Intestinal research, 2024)
Background/Aims: The impact of vaccination on inflammatory bowel disease (IBD) patients is still unknown, and no studies have assessed the changes in patient-reported outcomes (PROs) after vaccination in patients with IBD. Therefore, in this study, we investigated the impact of vaccines on the PROs of patients with IBD. Methods: We conducted a questionnaire survey of patients with IBD who visited outpatient clinics at 4 specialized IBD clinics of referral university hospitals from April 2022 to June 2022. A total of 309 IBD patients were included in the study. Patient information was collected from a questionnaire and their medical records, including laboratory findings, were reviewed retrospectively. Risk factors associated with an increase in PROs after COVID-19 vaccination were analyzed using logistic regression analyses. In addition, we assessed whether there were differences in variables by vaccine order using the linear mixed model. Results: In multivariate analysis, young age ( < 40 years) and ulcerative colitis (UC) were found to be independent risk factors for aggravation of PROs in patients with IBD. In all patients, platelet count significantly increased with continued vaccination in multiple pairwise comparisons. In UC patients, PROs such as the short health scale, UC-abdominal signs and symptoms, and UC-bowel signs and symptoms were aggravated significantly with continued vaccination. There was no significant increase in the variables of patients with Crohn’s disease.Conclusions: Therefore, there may be a need to counsel patients with IBD younger than 40 years of age, and patients with UC before they receive COVID-19 vaccinations.